Medición de la baja fecundidad: repensando los métodos demográficos - Ortega, José Antonio; Kholer, Hans-Peter (El Colegio de México A.C., 2007)
In a low fertility context there are a number of basic concepts that become more relevant for the analysis of fertility, such as parity progression analysis through life-table methods, here called fertility tables, and the consideration of the effects of tempo change on observed fertility rates. In this articles, these ideas are presented together with their historical genesis and their relationship to similar concepts such as demographic translation, together with examples of application to both period and cohort fertility analysis. Recent research, including research done by the authors, allow us today to estimate tempo-adjusted fertility intensities that can be used to obtain any tempo-adjusted period fertility measure or parity-progression fertility projections.